VARIASI MORFOLOGI POLEN DALAM MADU LEBAH Apis dorsata Fabr. YANG BERASAL DARI DESA HULU KELAY DAN DESA NYAPA INDAH KECAMATAN KELAY KABUPATEN BERAU - Mayasari, Fony; Stafrizal, Syafrizal; Susanto, Dwi (Jurusan Biologi, Fakultas Matematika dan Ilmu Pengetahuan Alam, 2016)
This research was conducted in November 2015 to March 2016 in Anatomy Laboratory and Plant Systematic. This study aims to determine the morphology of the pollen that contained in the liquid bees Apis dorsata Fabr. and to determine the type of plant food sources of honey bee Apis dorsata Fabr. Based on the results of research that has been conducted on a sample of honey bees Apis dorsata Fabr. from the villages of Hulu Kelay And Nyapa Indah, while the estimating pollen found as many as 22 Famillies and 29 species of plants. The honey samples from the Hulu Kelay’s has found 17 famillies and 23 species of plants. The dominant plant as feed for bees Apis dorsata Fabr. in the village of Hulu Kelay has found Family of Moraceae and species of Antiaris toxicaria totalling 98 pollen. Whereas in honey samples derived from village of Nyapa Indah has found 13 famillies and 15 species of plants. The dominant plant as feed for bees Apis dorsata Fabr. in the village of Nyapa Indah has found Family of Verbenaceae dan species of Vitex sp. totalling 90 pollen. Based on the morphology of the pollen (shape, size, ornament and arperture) and pollen with unit of monad dominates both samples. The shape are varies from oblate, suboblate, oblate spheroidal, prolate spheroidal, subprolate and prolate. Category size from small to large ornament consisting of psilate, perforate and echinate. Aperture consists of inaperture, monocolpate, monoporate, triporate, tricolpate, tricolporate and pantoporate.